Distribution, Composition, and Vertical Fluxes of Particulate Matter in Bays of Novaya Zemlya Archipelago, Vaigach Island at the End of Summer - N. V. Politova; V. P. Shevchenko; V. V. Zernova (Advances in Meteorology)
An analysis of suspended particulate matter (SPM) and phytoplankton distribution, composition and vertical particle fluxes in Russkaya Gavan’ Bay (Northern Island of the Novaya Zemlya), Bezymyannaya Bay (Southern Island of the Novaya Zemlya), Dolgaya Bay (northwestern part of the Vaigach Island) in comparison with the data from the Svalbard Archipelago is presented. Field studies were carried out by the authors during the 9th expedition of the RV “Professor Logachev” in September 1994, the 11th, 13th, and 14th expeditions of the RV “Akademik Sergey Vavilov” in September-October 1997 and August-September 1998. The data about Spitsbergen fjords are from literature. Our results show that, on the bays of the Barents Sea islands, most SPM stays in the bays (fjords) and only small part of it reaches the open sea. This is due to the hydrodynamic conditions in the bays, the large size of the particles, flocculation, and often to the morphological barriers in the relief at the bay entrances. It is important for ecological purposes to map out migration pathways of the SPM with pollutants from bays to the open sea. Results of our investigation indicate that the western bays of the Novaya Zemlya act as traps for SPM derived from glaciers and coastal abrasion.